ЭЛЕКТРОН ТАЪЛИМ МУҲИТИДА GEOGEBRA ДАСТУРИ ВОСИТАСИДА ЎҚИТИШ МЕТОДИКАСИНИ ТАКОМИЛЛАШТИРИШНИНГ ИЖТИМОИЙ ЗАРУРАТИ - Пренов, Б.Б.; Нурмаханов, К.Е. (SCIENCE and SOCIETY, 2022)
This article considers the modernization of the educational process, increasing the professional training of future teachers, and their requirements to use new methods and new pedagogical technologies.